A molten salt route to binder-free CeO2 on carbon cloth for high performance supercapacitors. (1st November 2022) - Jiang, Jia-Zhi; Gu, Yi-Jie; Wen, Wei; Ye, Zhizhen; Wu, Jin-Ming
Abstract: Cerium oxide is one of the most abundant and environment-benignity rare earth oxides, which is thus of interesting to explore its feasibility to serve as a safe and efficient candidate for supercapacitor electrodes. We report herein a facile one-step molten salt method to synthesize CeO2 nanoparticles abundant in surface oxygen vacancies, which are directly grown on a carbon cloth (CeO2 @CC). The CeO2 @CC exhibits a high specific capacitance of 811.5 mF cm −2 at the current density of 5 mA cm −2 in −0.8–0 V, with a good capacitance retention of 86.3 % at 5 mA cm −2 after 10, 000 cycles in 6 M KOH aqueous electrolyte. When assembled with a Co3 O4 @CC positive electrode, the Co3 O4 @CC//CeO2 @CC asymmetric supercapacitor achieves an energy density of 0.11 mWh cm −2 at a power density of 3.25 mW cm −2 . Both the abundant oxygen vacancies and the conductive carbon cloth contribute to the electrochemical performance. This work suggests that CeO2 could be a candidate material for high performance supercapacitors. Highlights: A facile one-step molten salt method deposits CeO2 nanoparticles on carbon cloth. The prepared CeO2 is abundant in surface oxygen vacancies. Optimized CeO2 @CC electrode delivers a specific capacitance of 811.5 mF cm −2 at 5 mA cm −2 . The Co3 O4 @CC//CeO2 @CC ASC achieves 0.11 mWh cm −2 @ 3.25 mW cm −2 .